Flexible Magnetoreceptors: Flexible Magnetoreceptor with Tunable Intrinsic Logic for On‐Skin Touchless Human‐Machine Interfaces (Adv. Funct. Mater. 25/2021). (17th June 2021) - Makushko, Pavlo; Oliveros Mata, Eduardo Sergio; Cañón Bermúdez, Gilbert Santiago; Hassan, Mariam; Laureti, Sara; Rinaldi, Christian; Fagiani, Federico; Barucca, Gianni; Schmidt, Nataliia; Zabila, Yevhen; Kosub, Tobias; Illing, Rico; et al.
Abstract : In article number 2101089, Gaspare Varvaro, Denys Makarov, and co‐workers present skin‐compliant touchless interactive devices based on spin‐valves with out‐of‐plane sensitivity to magnetic fields and with tunable logic characteristics. This technology will pave the way towards magnetoreceptive human‐machine interfaces or virtual‐ and augmented reality applications, which are intuitive to use, energy efficient, and insensitive to external magnetic disturbances.